AB0821 Baseline Characteristics of Patients with Moderate to Severe Psoriatic Arthritis: Post-Hoc Analysis of Responders vs Non-Responders to Etanercept. (9th June 2015) - Gisondi, P.; Girolomoni, G.; de Vlam, K.; Al Hammadi, A.; Carneiro, S.; Hsu, M.-A.; Szumski, A.; Jones, H.; Gallo, G.; Chhabra, A.
Abstract : Background: Exploration of baseline characteristics can guide decision-making by highlighting demographic and clinical variables, as well as patient-centred outcomes that may warrant adjustments to psoriatic arthritis (PsA) treatment. Psoriasis Randomized Etanercept STudy in Subjects with Psoriatic Arthritis (PRESTA) was a randomised, double blind study to evaluate the safety and efficacy of etanercept (ETN) on skin and joint disease in psoriasis (PsO) subjects with PsA (1). Objectives: An exploratory post-hoc analysis of data from PRESTA to examine baseline characteristics of patients who responded to ETN 50 mg twice weekly (BIW) for the initial 12 wks only followed by once weekly (QW) up to 24 wks (ETN 50mg BIW/QW). Methods: Baseline characteristics were analysed for Primary PsA response using minimal disease activity (MDA) (+enthesitis) defined as meeting 5 of the 7 following conditions: ≤1 tender joints; ≤1 swollen joints; Psoriasis Activity and Severity Index (PASI) ≤1 or body surface area ≤3; patient pain visual analogue score (VAS) ≤15; patient global disease activity VAS ≤20; health assessment questionnaire (HAQ) ≤0.5; tender entheseal points ≤1. MDA (−enthesitis) required meeting 5 out of 6 criteria with the 7th entheseal criteria excluded. Baseline characteristics were assessed for PsA response criteria (PsARC) and 50% improvement in the American College of Rheumatology Criteria (ACR50). Both continuous (using one-way ANOVA) and categorical (using Fisher's exact test) baseline characteristics were analysed for Wk 24 response parameters and not adjusted for multiple comparisons; results should be considered exploratory and not conclusive. Results: A total of 379 patients were included in this analysis. Several significant baseline characteristics of responders to ETN 50mg BIW/QW at Wk 24 were identified (Table ). Responders (MDA [−enthesitis], PsARC and ACR50) were all significantly younger than non-responders (Table ). Other than age, no other baseline characteristics were statistically significant for PsARC and ACR50 responders vs non-responders. There were significantly fewer female responders at Wk 24 vs non-responders for both MDA endpoints. Significantly more patients with oligoarthritis were responders vs non responders for both MDA endpoints (Table ). Compared with MDA (−enthesitis) non-responders, responders showed lower Physicians Global Assessment of PsA (52.6 vs 47.3; p<0.05). Improved HAQ scores (0.7 vs 1.0; p<0.001) were observed in MDA (-enthesitis) responders vs non-responders, respectively, and significantly lower (better) hospital anxiety and depression scale scores (HADS) for responders vs non-responders for both MDA endpoints (Table ). Conclusions: In this exploratory post-hoc analysis, age and gender, as well as many modifiable factors, were significantly different between responders and non-responders to ETN 50 mg BIW/QW. References: Sterry W, Ortonne JP, Kirkham B, et al. BMJ. 2010;340:c147. Acknowledgements: Medical writing support was provided by Neel Misra of Engage Scientific Solutions and was funded by Pfizer Inc. Disclosure of Interest: P. Gisondi Speakers bureau: Abbvie, Pfizer, Jannsen, Novartis, Eli Lilly, MSD, G. Girolomoni Grant/research support from: AbbVie, Amgen, Bioderma, Celgene, Janssen, L'Oreal, MSD, Novartis, Pierre Fabre, Pfizer, Regeneron, Roche, Consultant for: AbbVie, Actelion, Allmirall, Amgen, Bioderma, Boehringer Ingelheim, Celgene, Dompè, Galderma, Janssen, Leo Pharma, Eli Lilly, Maruho, Merck-Serono, MSD, Mundipharma, Novartis, Otsuka, Pfizer, Pierre Fabre, Rottapharm, Shiseido, Speakers bureau: AbbVie, Actelion, Allmirall, Amgen, Bioderma, Boehringer Ingelheim, Celgene, Dompè, Galderma, Janssen, Leo Pharma, Eli Lilly, Maruho, Merck-Serono, MSD, Mundipharma, Novartis, Otsuka, Pfizer, Pierre Fabre, Rottapharm, Shiseido, K. de Vlam Consultant for: Pfizer, Abbott, MSD, Celgene, Janssen, UCB, Speakers bureau: Pfizer, MSD, AbbVie, UCB, Celgene, A. Al Hammadi: None declared, S. Carneiro: None declared, M.-A. Hsu Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., A. Szumski Consultant for: Pfizer Inc., H. Jones Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., G. Gallo Shareholder of: Pfizer Inc., Employee of: Pfizer Europe, A. Chhabra Shareholder of: Pfizer Inc., Employee of: Pfizer Inc.